Terraced memorial dedicated to Martyrs - Ghosh, Ayan (Jio Institute, 2023)
Marble memorial at Hutatma Chowk dedicated to martyrs who laid down their lives on 21 November 1955, when demonstrators at Flora Fountain were fired upon by security forces during the period of agitation for Samyukta Maharashtra Movement (Movement for United Maharashtra).